Spatiotemporal patterns and surveillance artifacts in maternal mortality in the United States: a population-based studyResearch in context - K.S. Joseph; Sarka Lisonkova; Amélie Boutin; Giulia M. Muraca; Neda Razaz; Sid John; Yasser Sabr; Sophie Simon; Johanna Kögl; Elizabeth A. Suarez; Wee-Shian Chan; Azar Mehrabadi; et al. (Elsevier, 2024)
Summary: Background: Reports of high and rising maternal mortality ratios (MMR) in the United States have caused serious concern. We examined spatiotemporal patterns in cause-specific MMRs, in order to obtain insights into the cause for the increase. Methods: The study included all maternal deaths recorded by the Centers for Disease Control and Prevention from 1999 to 2021. Changes in overall and cause-specific MMRs were quantified nationally; in low-vs high-MMR states (i.e., MMRs <20 vs ≥26 per 100,000 live births in 2018-2021); and in California vs Texas (populous states with low vs high MMRs). Cause-specific MMRs included those due to unambiguous causes (e.g., selected obstetric causes such as pre-eclampsia/eclampsia) and less-specific/potentially incidental causes (e.g., "other specified pregnancy-related conditions", chronic hypertension, and malignant neoplasms). Findings: MMRs increased from 9.60 (n = 1543) in 1999-2002 to 23.5 (n = 3478) per 100,000 live births in 2018-2021. The temporal increase in MMRs was smaller in low-MMR states (from 7.82 to 14.1 per 100,000 live births) compared with high-MMR states (from 11.1 to 31.4 per 100,000 live births). MMRs due to selected obstetric causes decreased to a similar extent in low-vs high-MMR states, whereas the increase in MMRs from less-specific/potentially incidental causes was smaller in low- vs high-MMR states (MMR ratio (RR) 5.57, 95% CI 4.28, 7.25 vs 7.07, 95% CI 5.91, 8.46), and in California vs Texas (RR 1.67, 95% CI 1.03, 2.69 vs 10.8, 95% CI 6.55, 17.7). The change in malignant neoplasm-associated MMRs was smaller in California vs Texas (RR 1.21, 95% CI 0.08, 19.3 vs 91.2, 95% CI 89.2, 94.8). MMRs from less-specific/potentially incidental causes increased in all race/ethnicity groups. Interpretation: Spatiotemporal patterns of cause-specific MMRs, including similar reductions in unambiguous obstetric causes of death and variable increases in less-specific/potentially incidental causes, suggest misclassified maternal deaths and overestimated maternal mortality in some US states. Funding: This work received no funding.